Navigating Barriers and Empowering Women in Sharia MSMEs: A Qualitative Study on Entrepreneurial Housewives in Samarinda - Sari, Purnama; Mursyid, Mursyid (IAIN Manado, 2025)
Women, particularly housewives, play an increasingly vital role in the development of Sharia-based micro, small, and medium enterprises (MSMEs). However, most existing studies focus on women’s entrepreneurship in general and seldom examine the specific barriers and empowerment experiences of housewives within the Sharia MSME context. This study aims to explore the challenges, empowerment strategies, and socio-religious dynamics experienced by entrepreneurial housewives in Samarinda. Using a qualitative literature review approach, this research synthesizes national and international studies published between 2000 and 2025. The analysis identifies four main dimensions shaping housewives’ participation in Sharia MSMEs: access to Islamic microfinance, digital literacy, social capital, and the internalization of Islamic ethical values in business practices. The findings show that while housewives hold a strategic role in fostering Sharia MSME growth, they face persistent constraints such as limited access to capital, low technological competence, and the double burden of domestic responsibilities. Nonetheless, religious motivation, community-based support systems, and Sharia-oriented social networks serve as strong empowerment enablers. The study concludes that sustainable empowerment of housewives in Sharia MSMEs requires integrative policies that enhance financial literacy, provide flexible Sharia-compliant microfinancing, and strengthen digital entrepreneurship training through community engagement. This research contributes new insights for policymakers, Islamic financial institutions, and women’s organizations aiming to promote inclusive, faith-based economic participation among housewives.